ON THE TYPE CORRECTNESS OF POLYMORPHIC λ-TERMS. 1 - Arakelyan, A. H. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In this paper polymorphic lambda terms are considered, where no type information is provided for the variables. The aim of this work is to extend the algorithm of typification [1] of such terms introducing type constants and term constants.
Keywords: type; term; constraint; skeleton; expansion; typing